2023
DOI: 10.1002/edm2.408
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between adipokine levels and bone mass—A systematic review

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
0
10
0
1
Order By: Relevance
“…However, it is typically the lean body mass that has a positive effect on bone health, rather than fat mass (Ho-Pham et al, 2014, Nguyen et al, 2020). Nevertheless, the connection between skull bone thickness and adiposity might involve the effects of adipokines (i.e., cytokines produced by the adipocytes) on bone mass (Mangion et al 2023) and further studies are needed to elucidate this finding.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is typically the lean body mass that has a positive effect on bone health, rather than fat mass (Ho-Pham et al, 2014, Nguyen et al, 2020). Nevertheless, the connection between skull bone thickness and adiposity might involve the effects of adipokines (i.e., cytokines produced by the adipocytes) on bone mass (Mangion et al 2023) and further studies are needed to elucidate this finding.…”
Section: Discussionmentioning
confidence: 99%
“…As an underlying mechanism, in vitro studies suggested that leptin exerts direct osteogenic effects mediated by its receptors in osteoblasts and osteoclasts [64][65][66] . Published data regarding the effects of leptin on bone parameters are however contradictory showing both anti-osteogenic as well as anabolic effects on bone formation (for reviews see 67,68 ). In the present study, partial correlation analyses revealed a significant negative association between leptin and BMC in men after adjusting for weight (with BMD and T-Score showing a trend towards significance) confirming a sex-specific effect of this hormone.…”
Section: Discussionmentioning
confidence: 99%
“…Also, bone metabolism and other effects are regulated by adipokines, whose levels increase or decrease in response to exercise [66 ], and the main effects of adipokines on the skeletal system are shown in Figure 2. Leptin's ability to regulate the expression of the receptor activator of nuclear factor KB ligand (RANKL) and neuropeptides in the hypothalamus and induce activation of the sympathetic nervous system gives it the ability to modulate bone formation [3,67]. The ratio of RANKL to osteoprotegerin (OPG), a substance secreted by osteoblasts, is important in bone remodelling [20].…”
Section: Skeletal Systemmentioning
confidence: 99%
“…In addition to their effects on metabolic regulation, increasing attention is being paid to the systemic effects of adipokines on the body. These include the impact on whole systems, such as the muscular, skeletal, immune, and cardiovascular systems, and on processes like spermatogenesis, insulin resistance, and tumorigenesis [3,4].…”
Section: Introductionmentioning
confidence: 99%